12. Neurophysiology and treatment of dystonia: Non-invasive brain stimulation studies. Issue 3 (March 2015) - Ziemann, Ulf
<x xml:space="preserve">Abstract</x> Focal hand dystonia (FHD) is characterized by task-dependent involuntary co-contraction of hand muscles. Functional MRI studies demonstrated excessive activation of primary sensorimotor cortex during dystonic motor action while premotor cortex and supplementary motor area are underactive. Transcranial magnetic stimulation (TMS) has substantially contributed to our understanding of the cortical pathophysiology underlying these abnormalities. These TMS studies will be reviewed in this presentation. Motor evoked potentials (MEP) are significantly stronger facilitated during voluntary target muscle contraction in FHD compared to healthy controls, indicating hyperexcitability of the corticospinal system. The cortical silent period (CSP), a marker of GABABergic inhibition in motor cortex is shortened during dystonic contractions in FHD, and short-interval intracortical inhibition (SICI), a marker of GABAAergic inhibition in motor cortex is reduced in FHD, indicating significant alteration of inhibitory motor cortical control. The long-latency afferent inhibition (LAI) is reduced in FHD, indicating that central processing of sensory input is abnormal. Finally, surround inhibition is reduced in FHD, supporting the idea that this alteration may be a principal pathophysiological mechanism of activity spillover to antagonist muscles in dystonia. In addition to measuring motor cortical excitability, repetitive TMS can also be employed for induction of plasticity. It was found that patients with FHD display exaggerated levels of LTP-like plasticity. In addition, while healthy subjects show homeostatic control of plasticity, FHD patients often exhibit non-homeostatic metaplasticity that may lead to non-physiological run-away plasticity. Finally, FHD patients display a failure of depotentiation of LTP-like plasticity, which may contribute to the inability to erase or correct unwanted motor activation patterns once they have been encoded. In summary, TMS research has provided detailed knowledge on the cortical pathophysiology of dystonia. The data support the notion that hyperexcitability, disturbed inhibition, altered sensorimotor integration and abnormal regulation of synaptic plasticity significantly contribute to the clinical picture of dystonia. In the final part of this presentation, initial studies will be presented that use repetitive TMS as a therapeutic tool for treatment of dystonia aiming at correcting these abnormalities of motor cortex excitability and plasticity.